Corporate Social Responsibility dalam Memediasi Pengaruh Green Accounting dan Good Corporate Governance terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sektor Energi di Indonesia - Dimas Saukas Pribadi; Wahyuni, Lidia; Amalina, Nurhafifah (Ekonomi Digital, 2026)
Sustainability practices and sound corporate governance have become crucial in improving financial performance, particularly in the energy manufacturing sector, which has a significant environmental impact. This study aims to analyze the role of Corporate Social Responsibility in mediating the influence of Green Accounting and Good Corporate Governance on financial performance in energy manufacturing companies in Indonesia. CSR is positioned as a mediating variable that connects sustainability practices and governance to financial performance, which is measured using Return on Assets. This research employs a quantitative approach using secondary data from 27 companies based on annual reports covering the period 2020–2024. The findings indicate that Green Accounting and GCG have a significant influence on CSR, and that Corporate Social Responsibility positively affects financial performance. These results provide practical implications for companies in formulating sustainability strategies, and serve as a reference for investors and regulators in assessing the quality of corporate governance and social responsibility.